2020
DOI: 10.1002/ldr.3703
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating aggregate stability, surface properties and disintegration behaviour of bauxite residue induced by Ca/Na

Abstract: Bauxite residue, a typical industrial solid waste which contains a large amount of Na+, is usually physically degraded. Understandings of aggregate formation, which is a critical process in soil development, are essential to facilitate ecological rehabilitation on the disposal areas. However, few studies have investigated the aggregation behaviour and mechanisms of key salt ions (Ca2+ and Na+) in residue aggregates. Therefore, an integrated method of Le Bissonnais' method, the combined determination method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…In addition, companied with the transform of the aggregates' morphology from the loose microstructure (CK) to a soil-like structure appearance (HS3) (Figure 7C), there was a markable increase for the distribution of Ca, Fe and Al elements on the aggregate surface (Figures 7A,B). It showed that Ca 2+ had a good affinity with the soil colloidal surface, which could reduce the dispersion of clays, and promote the flocculation and stability of aggregates (Harris and Rengasamy, 2004;Xue et al, 2021). So that, beside of the directive cohesion between aggregates, Increasing the level of Fe/Al oxides and Ca 2+ also is principal way for organic amendment to promote the aggregation of fine bauxite residue particles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, companied with the transform of the aggregates' morphology from the loose microstructure (CK) to a soil-like structure appearance (HS3) (Figure 7C), there was a markable increase for the distribution of Ca, Fe and Al elements on the aggregate surface (Figures 7A,B). It showed that Ca 2+ had a good affinity with the soil colloidal surface, which could reduce the dispersion of clays, and promote the flocculation and stability of aggregates (Harris and Rengasamy, 2004;Xue et al, 2021). So that, beside of the directive cohesion between aggregates, Increasing the level of Fe/Al oxides and Ca 2+ also is principal way for organic amendment to promote the aggregation of fine bauxite residue particles.…”
Section: Discussionmentioning
confidence: 99%